Effectiveness of the flash glucose monitoring system in preventing severe hypoglycemic episodes and in improving glucose metrics and quality of life in subjects with type 1 diabetes at high risk of acute diabetes complications - Dei Cas, Alessandra; Aldigeri, Raffaella; Bellei, Giulia; Raffaeli, Davide; Di Bartolo, Paolo; Sforza, Alessandra; Marchesini, Giulio; Ciardullo, Anna Vittoria; Manicardi, Valeria; Bianco, Maurizio; Monesi, Marcello; Vacirca, Anna; et al. (Acta diabetologica, 2024)
Aims To assess the effectiveness of the intermittent-scanned continuous glucose monitoring (isCGM) system in preventing severe hypoglycemic episodes and in improving glucose parameters and quality of life. Methods Four hundred T1D individuals were enrolled in a prospective real-word study with an intermittently scanned continuous glucose monitoring device during the 12-months follow-up. The primary endpoint was the incidence of severe hypoglycemic events. Results 82% of subjects were naïve to the use of the device (group A) and 18% were already wearing the system (group B). The cumulative incidence of severe hypoglycemia (SH) at 12 months was 12.06 per 100 person-year (95% CI: 8.35–16.85) in group A and 10.14 (95% CI: 4.08–20.90) in group B without inter-group differences. In group A there was a significant decrease in SH at 12 months compared to 3 months period ( p = 0.005). Time in glucose range significantly increased in both groups accompanied with a significant decrease in glucose variability. HbA1c showed a progressive significant time-dependent decrease in group A. The use of the device significantly improved the perceived quality of life. Conclusion This study confirmed the effectiveness of the isCGM in reducing hypoglycemic risk without glucose deterioration, with potential benefits on adverse outcomes in T1D individuals. Trial registration : ClinicalTrials.gov registration no. NCT04060732.